The Effect of User Interface, User Experience, and Perceived Ease of Use on Interest in Using the SOCO by Sociolla Application with Perceived Usefulness as a Moderator - Pidada, Ida Ayu Iswari; Cahaya Dewi, Ni Putu Novia (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This research aims to determine the effect of user interface, user experience, and perceived ease of use on interest in use and to determine the moderating role of perceived usefulness in the relationship between user interface, user experience, and perceived ease of use with interest to use. The sample in this study consisted of people in Denpasar City who knew Sociolla and could download the SOCO by Sociolla application, as many as 105 people. The data analysis technique uses the Validity Test, Reliability Test, Classical Assumption Test, Coefficient of Determination Test (R2), t-test, and Hayes Process Moderation Model. From the research results obtained, the user interface has a positive and significant effect on interest to use, user experience has a positive and significant impact on interest to use, perceived ease of use has a significant positive impact on interest to use, perceived usefulness moderates the relationship between the user interface and interest to use, perceived usefulness moderates the relationship between user experience and interest to use and perceived usefulness moderates the relationship between perceived ease of use and interest in using. Researchers can suggest that SOCO by Sociolla is expected to always make applications with an attractive appearance and design, create a system that can provide a fast response, contains complete features, and is easy to use, and make applications with many benefits and advantages.